Exploring Community Based Responses and the Natural History of a Drug Market - Wes Abercrombie; Mitchell Mackinem (Social Work and Society, 2015)
Previous studies portray open drug market neighborhoods as uniformly poor, urban, socially disorganized, with weak informal social control. Further, open drug market neighborhoods appear sui genesis. Based on field data collected over a multiyear study of a neighborhood with an open drug market area we question the universality of these previous characterizations of drug market neighborhoods. We examined a community that became a drug market place not because of breakdown in social control, but as a product of strong informal social control tied with traditional family values. The strong informal social control did not diminish the progression to an open drug market areas but propelled the movement and ultimately instigated the return to a non-criminal location. Our research suggests that not all neighborhood drug markets are necessarily the product of linear progression from organized to disorganized neighborhoods. While the generalizability of these findings are not established, we suggest it may support the possibility that the formation of some open drug markets may be a multi-linear process with diverse manifestations. We suggest such phenomena may support both Community Policing and Community Social Work paradigms. As such, this study could identify future directions for some research addressing alternative origins, maintenance and control of some neighborhood hosted drug markets.